2014
DOI: 10.1111/1755-5922.12049
|View full text |Cite
|
Sign up to set email alerts
|

Disease Modifying Therapies Modulate Cardiovascular Risk Factors in Patients with Multiple Sclerosis

Abstract: SUMMARYObjectives: This retrospective study aimed to determine (1) the association between the use of three major disease modifying therapies (DMTs) (Interferon-beta [IFN-b], Glatiramer acetate [GA], Natalizumab [NTZ]) and cardiovascular (CV) risk factors in multiple sclerosis (MS) patients, and (2) the association between the use of CV drugs (antihypertensive, hypolipidemic, and antiplatelets) and other drugs acting on the CV system (antispastics/anticonvulsants/anxyolitics, antidepressants/stimulants), and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
1
30
1
1
Order By: Relevance
“…A study by Sternberg and colleagues which compared the lipid profile difference between MS patients who were on disease modifying therapies (DMTs-users) and DMTs-naïve demonstrated a significantly higher HDL in DMTs-users compared to DMTs-naïve. The level of TC and LDL were higher in DMTs-users but not significantly different [48].…”
Section: Lipids In People With Ms and Comparison With Healthy Populatmentioning
confidence: 68%
See 4 more Smart Citations
“…A study by Sternberg and colleagues which compared the lipid profile difference between MS patients who were on disease modifying therapies (DMTs-users) and DMTs-naïve demonstrated a significantly higher HDL in DMTs-users compared to DMTs-naïve. The level of TC and LDL were higher in DMTs-users but not significantly different [48].…”
Section: Lipids In People With Ms and Comparison With Healthy Populatmentioning
confidence: 68%
“…In another study of 430 MS patients by Marrie and colleagues, the age-adjusted prevalence of hypertension in the MS patients was similar to that of the general population (MS: 20.8% versus general population: 22.5% [PR: 0.9; 95% CI: 0.78-1.06]). Studies reporting actual blood pressure values recorded similar values in MS patients compared to controls [8,48,53]. Sternberg and colleagues also reported that there was no significant difference in the use of antihypertensive drugs between MS and non-MS patients.…”
Section: Prevalence Of Hypertension In People With Ms and Comparison mentioning
confidence: 88%
See 3 more Smart Citations